Principles of building a new ecosystem: Economic, legal and social aspects - Danilchenko S. L., Sudakova N. E., Kurdiumov A. V., Gromova N. S., Kruglov V. N., Astafurova O. A., Kulagina I. I., Malov M. S., Ushakova O. A., Kostenko E. G., Medvedeva N. V., Meshcheriagina V. A., Vilacheva M. N., Balkovaia V. G., Lankova V. A., Ponikarovskaya V. V., Paniushkina M. A., Kvasov V. B., Sizova A. S., Babushkin E. R., Semenova S. S. (Principles of building a new ecosystem: Economic, legal and social aspects, 2024)
in the present study, the authors devoted their attention to the development of theoretical and methodological foundations for the formation of a cluster of small and medium-sized businesses in a competitive environment at the regional level. The object of the study is small and medium-sized businesses in the competitive environment of the region (on the example of the Sverdlovsk region). The subject is the circle of public relations related to the formation of a strategy for the development of small and medium-sized businesses in the competitive environment of the region. The authors solved the problems of revealing the essence of small and medium-sized businesses, as well as its role in the national economy. Approaches to assessing the effectiveness of support for small and medium-sized businesses are considered. An analysis of the current state of small and medium-sized businesses in Russia in general and in the Sverdlovsk region in particular was carried out. Measures aimed at the development of small and medium-sized businesses at the regional level were proposed, as well as an assessment was given to them.
Keywords: кластер; государственная поддержка; малое предпринимательство; среднее предпринимательство; Свердловская область; вызовы; угрозы; threats; cluster; small enterprise; medium-sized enterprise; Sverdlovsk region; government support; calls